Diabetic kidney disease in type 2 diabetes: a review of pathogenic mechanisms, patient-related factors and therapeutic options - Woodhams, Louise; Sim, Tin Fei; Chalmers, Leanne; Yeap, Bu; Green, Daniel; Schlaich, Markus; Schultz, Carl; Hillis, Graham (PeerJ, 2021)
The global prevalence of diabetic kidney disease is rapidly accelerating due to an increasing number of people living with type 2 diabetes. It has become a significant global problem, increasing human and financial pressures on already overburdened healthcare systems. Interest in diabetic kidney disease has increased over the last decade and progress has been made in determining the pathogenic mechanisms and patient-related factors involved in the development and pathogenesis of this disease. A greater understanding of these factors will catalyse the development of novel treatments and influence current practice. This review summarises the latest evidence for the factors involved in the development and progression of diabetic kidney disease, which will inform better management strategies targeting such factors to improve therapeutic outcomes in patients living with diabetes.
Keywords: Type 2 Diabetes Mellitus; Diabetic kidney disease; Pathogenesis; Risk factors